"Feeling Warmth and Close to Her": Communication and Resilience Reflected in Turning Points in Positive Adult Stepchild–Stepparent Relationships. Issue 2 (3rd April 2018) - Braithwaite, Dawn O.; Waldron, Vincent R.; Allen, Jordan; Oliver, Bailey; Bergquist, Gretchen; Storck, Katie; Marsh, Jaclyn; Swords, Nathan; Tschampl-Diesing, Carol
ABSTRACT: With the goal of understanding the development of positive stepchild–stepparent relationships, the researchers focused on turning points characterizing the interaction of adult stepchildren who have a positive bond with a stepparent. Engaging a relational turning points perspective, 38 stepchildren (males and females, ages 25 to 52 years old) who reported a positive stepparent relationship were interviewed, generating 269 turning points which were categorized into 15 turning point types and coded by valence. Turning points occurring most frequently were: prosocial actions, quality time, conflict/disagreement, changes in household/family composition, and rituals. Findings are discussed, including implications for developing and enacting resilient and positive stepchild–stepparent relationships and future directions for researchers wanting to focus on positive family interaction.